Association Between Locoregional Private Equity Investment in Retina Practices and Academic Vitreoretinal Caseload - Franco JJ; Pan WW; Mian SI; Wubben TJ (Clinical Ophthalmology)
Jovany J Franco,* Warren W Pan,* Shahzad I Mian, Thomas J Wubben Department of Ophthalmology and Visual Sciences, Kellogg Eye Center, University of Michigan, Ann Arbor, MI, USA*These authors contributed equally to this workCorrespondence: Thomas J Wubben, Department of Ophthalmology and Visual Sciences University of Michigan Kellogg Eye Center, 1000 Wall Street, Ann Arbor, MI, 48105, USA, Email twubben@med.umich.eduPurpose: Private equity (PE) firms acquire stakes in non-publicly traded companies to generate value through operational improvements. PE ownership of US ophthalmic practices has expanded rapidly over the past decade. Despite debate regarding the perceived benefits and drawbacks of PE, limited data exists regarding its impact on patients and practices. In particular, there remains a dearth of literature assessing the impact of PE acquisition on non-PE practices; herein, we assess the effect of locoregional PE investment on the rate of pars plana vitrectomy (PPV) for retinal detachment (RD) repair performed at a US academic center.Methods: Patients who underwent RD PPV (Current Procedural Terminology [CPT] codes 67108 or 67113) or routine PPV (reference group; CPT 67040, 67041, or 67042) at a single US academic center from 01/01/2013 to 12/31/2023 were identified. Patients’ census tract of residence was classified as PE-exposed or PE-unexposed if within 30-min of a PE-exposed or PE-unexposed retina practice, respectively. Estimates of the association between PE exposure and yearly, tract-level RD PPV and routine PPV case rate were generated through difference-in-differences (DiD) analyses via calculation of the average treatment effect on the treated (ATT) (ie, the estimated difference in yearly, tract-level case rate in PE-exposed tracts following exposure compared to the expected rate if those tracts were to have remained unexposed).Results: Covariate-controlled DiD estimation of the association between PE exposure and tract-level RD PPV case rate revealed a statistically significant ATT of 8.93 cases/million residents/year (95% CI: [0.79– 17.08], p = 0.03). No significant association was seen for routine PPVs (ATT = 0.30, 95% CI: [− 4.54– 5.14], p = 0.90). Using the 2023 population for PE-exposed tracts (6.94 million), the observed ATT for RD PPVs suggests approximately 33.9% of cases (62/183) from PE-exposed tracts in 2023 were associated with PE exposure.Conclusions/Relevance: Locoregional PE investment in retina practices is associated with an increase in RD PPVs at a nearby academic center. Expanded collaboration between academic centers, non-PE private practices, and PE groups is needed to ensure communities maintain access to core vitreoretinal services.Keywords: service area analysis, private equity, geocoding, health economics, retinal detachment, pars plana vitrectomy, difference-in-differences, PPV, RD, DiD, PE